Impact of the fear of catching COVID-19 on mental health in undergraduate students: a predictive model for anxiety, depression, and insomnia - Vilca, Lindsey W. (2022)
Most studies only describe mental health indicators (anxiety, depression, insomnia, and stress) and the risk factors associated with these indicators during the pandemic (sex, student status, and specific physical symptoms). However, no explanatory studies have been found that assess the impact of variables associated with COVID-19. Against this background, the objective of the study was to evaluate the impact of the fear of catching COVID-19 on the level of anxiety, depression, and insomnia in 947 university students of both sexes (41.6% males and 58.4% females) between the ages of 18 and 35 (M = 21.6; SD = 3.4). The Fear of catching COVID-19 Scale, the Generalized Anxiety Disorder Scale (GAD-7), the Patient Health Questionnaire (PHQ-9), and the Insomnia Severity Index (ISI) were used to measure the variables. The results of the study show that the fear of catching COVID-19 significantly influences the level of anxiety (β =.52; p <.01), insomnia (β =.44; p<.01), and depression (β =.50; p <.01) experienced by university students (χ2 = 2075.93; df = 371; p =.000; RMSEA =.070 [CI 90%.067–.073]; SRMR =.055; CFI =.95; TLI =.94). The descriptive results show that a notable percentage of university students present significant symptoms of anxiety (23%), depression (24%), and insomnia (32.9%). It is concluded that the fear of catching COVID-19 is a serious health problem since it influences the appearance of anxiety, depression and insomnia symptoms. © 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.